PENGELOLAAN ISU PEMILIHAN UMUM PRESIDEN REPUBLIK INDONESIA TAHUN 2019 PADA MEDIA DI JAWA TENGAH - Agung Wibiyanto; Wahyu Tri Hastiningsih (Fakultas Ushuluddin dan Dakwah UIN Raden Mas Said Surakarta, 2019)
This study is to review the political issues that arise in Central Java and analyze several issues based on framing analysis and the media agenda. The type of this research is descriptive qualitative. The data are analyzed from five journalists, that are Solo Pos, Tribun Jawa Tengah, and Kedaulatan Rakyat in interviews session. The results of this study mention the issues that arise, include the issue of identity politics, the issue of the president profile 2019, the policy issue of three magic cards and single card, the tagline of #2019GantiPresiden, the issue of total war, the issue of moving the Prabowo-Sandi winning headquarters to Java Middle, people power and coup issue. These issues are detailed by framing and also the media setting agenda to be taken into consideration the news material. The contribution in this research is to review the detailed management of issues that have arisen around the 2019 presidential election.